Smokeless Tobacco Point of Sale Advertising, Placement and Promotion: Associations With Store and Neighborhood Characteristics - Shirley A. James; John G. Heller; Chantel J. Hartman; Andrew C. Schaff; Nasir Mushtaq; Laura A. Beebe (Frontiers Media S.A., 2021)
Introduction: Objectives of this study were to determine retail and neighborhood characteristics associated with smokeless tobacco (ST) product promotion, price promotion, and storefront advertising among retailers in Oklahoma.Methods: In this statewide point-of-sale study, we collected data from 1,354 ST retailers. Using store characteristics and census tract information, we estimated summary statistics and adjusted prevalence ratios during 2019-2020.Results: Of ST retailers audited, 11.0% demonstrated ST youth promotion, 43.0% ST price promotions, and 19.6% ST storefront advertising. The adjusted prevalence ratio (aPR) for convenience stores was higher for all three ST strategies: youth promotion (aPR = 3.4, 95% CI 1.9, 6.2), price promotion (aPR = 3.8, 95% CI 2.9, 5.0), and storefront advertising (aPR=16.4, 95% CI 6.7, 40.3) compared to other store types. Metropolitan tobacco retailers had higher aPRs for youth promotion (aPR = 1.7, 95% CI 1.12 2.6) and storefront advertising (aPR = 1.5, 95% CI 1.2, 1.9).Conclusions: Findings of this study suggest there are currently ample opportunities for youth and adults at risk for tobacco initiation to be exposed to ST products in the retail environment. Convenience stores, more likely to be found and utilized in rural areas compared to metropolitan areas, are disproportionately more likely to engage in marketing strategies that could lure youth into trying smokeless tobacco.